Regional Pericarditis Mimicking Inferior Myocardial Infarction following Abdominal Surgery - Ahmad T. Alhammouri; Bassam A. Omar (Case Reports in Medicine)
Acute pericarditis is common but illusive, often mimicking acute coronary syndrome in its clinical and electrocardiographic presentation. Regional pericarditis, though rare, presents further challenge with a paucity of published diagnostic criteria. We present a case of postoperative regional pericarditis and discuss helpful electrocardiographic findings. A 66-year-old male with history of open drainage of a liver abscess presented with abdominal pain and tenderness. CT of the abdomen was concerning for pneumatosis intestinalis of the distal descending colon. He underwent lysis of liver adhesions; exploration revealed only severe colonic impaction, for which he had manual disimpaction and peritoneal irrigation. Postoperatively, he developed sharp chest pain. Electrocardiogram revealed inferior ST elevation. Echocardiogram revealed normal left and right ventricular dimensions and systolic function without wall motion abnormalities. Emergent coronary angiography did not identify a culprit lesion, and left ventriculogram showed normal systolic function without wall motion abnormalities. He received no intervention, and the diagnosis of regional pericarditis was entertained. His cardiac troponin was 0.04 ng/dL and remained unchanged, with resolution of the ECG abnormalities in the following morning. Review of his preangiography ECG revealed PR depression, downsloping baseline between QRS complexes, and reciprocal changes in the anterior leads, suggestive of regional pericarditis.